Inhibition of platelet activation and thrombus formation by adenosine and inosine: studies on their relative contribution and molecular modeling. - Eduardo Fuentes; Jaime Pereira; Diego Mezzano; Marcelo Alarcón; Julio Caballero; Iván Palomo (PLoS ONE, 2014)
The inhibitory effect of adenosine on platelet aggregation is abrogated after the addition of adenosine-deaminase. Inosine is a naturally occurring nucleoside degraded from adenosine.The mechanisms of antiplatelet action of adenosine and inosine in vitro and in vivo, and their differential biological effects by molecular modeling were investigated.Adenosine (0.5, 1 and 2 mmol/L) inhibited phosphatidylserine exposure from 52±4% in the control group to 44±4 (p<0.05), 29±2 (p<0.01) and 20±3% (p<0.001). P-selectin expression in the presence of adenosine 0.5, 1 and 2 mmol/L was inhibited from 32±4 to 27±2 (p<0.05), 14±3 (p<0.01) and 9±3% (p<0.001), respectively. At the concentrations tested, only inosine to 4 mmol/L had effect on platelet P-selectin expression (p<0.05). Adenosine and inosine inhibited platelet aggregation and ATP release stimulated by ADP and collagen. Adenosine and inosine reduced collagen-induced platelet adhesion and aggregate formation under flow. At the same concentrations adenosine inhibited platelet aggregation, decreased the levels of sCD40L and increased intraplatelet cAMP. In addition, SQ22536 (an adenylate cyclase inhibitor) and ZM241385 (a potent adenosine receptor A2A antagonist) attenuated the effect of adenosine on platelet aggregation induced by ADP and intraplatelet level of cAMP. Adenosine and inosine significantly inhibited thrombosis formation in vivo (62±2% occlusion at 60 min [n = 6, p<0.01] and 72±1.9% occlusion at 60 min, [n = 6, p<0.05], respectively) compared with the control (98±2% occlusion at 60 min, n = 6). A2A is the adenosine receptor present in platelets; it is known that inosine is not an A2A ligand. Docking of adenosine and inosine inside A2A showed that the main difference is the formation by adenosine of an additional hydrogen bond between the NH2 of the adenine group and the residues Asn253 in H6 and Glu169 in EL2 of the A2A receptor.Therefore, adenosine and inosine may represent novel agents lowering the risk of arterial thrombosis.